Evaluation of the effect of financial literacy (financial awareness, financial capability and financial behavior) on investment decisions in micro, small and medium enterprises (MSMEs) in indonesia - Dadan Sumantri; Radiyul Fahmi; Maya Sari (Institute of Computer Science (IOCS), 2024)
Especially when it comes to Micro, Small, and Medium-Sized Enterprises (MSMEs) in Indonesia, financial literacy is crucial in guiding investment decisions. In this quantitative study, the relationship between MSME owners' and managers' investment decisions and the elements of financial literacy—financial knowledge, financial competence, and financial behavior—is examined. Data from the survey were analysed using Structural Equation Modelling with Partial Least Squares (SEM-PLS), and 164 respondents made up the sample. The results demonstrate that investing decisions are influenced by a combination of financial behaviour, financial competence, and financial awareness. Specifically, more informed, strategic, and cautious investing choices are linked to better financial literacy levels. The findings of this study demonstrate how crucial it is to raise financial literacy among Indonesia's MSMEs in order to foster competitiveness and economic growth. For practitioners, policymakers, and business owners who wish to equip MSMEs with the financial literacy and decision-making abilities necessary for wise investment choices, this study offers insightful information